2014
DOI: 10.3766/jaaa.25.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Mechanisms of Tinnitus: Review and Clinical Implications

Abstract: Background The study of tinnitus mechanisms has increased tenfold in the last decade. The common denominator for all of these studies is the goal of elucidating the underlying neural mechanisms of tinnitus with the ultimate purpose of finding a cure. While these basic science findings may not be immediately applicable to the clinician who works directly with patients to assist them in managing their reactions to tinnitus, a clear understanding of these findings is needed to develop the most effective procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
180
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(192 citation statements)
references
References 208 publications
(293 reference statements)
5
180
0
7
Order By: Relevance
“…prevalence, aetiology, and potential treatments). This is, at least in part, a consequence of the subjective nature of tinnitus assessment, the heterogeneity of the question used to define the presence of tinnitus, and the large variety of tinnitus characteristics [3] and associated disorders [4]. …”
Section: Introductionmentioning
confidence: 99%
“…prevalence, aetiology, and potential treatments). This is, at least in part, a consequence of the subjective nature of tinnitus assessment, the heterogeneity of the question used to define the presence of tinnitus, and the large variety of tinnitus characteristics [3] and associated disorders [4]. …”
Section: Introductionmentioning
confidence: 99%
“…In this context, both the orientation and the application of questionnaires are of great importance at this moment, since they make possible the knowledge of patients' fragilities, as well as the effects of tinnitus on their social activities, their emotions, their work performance and their communicative abilities (25) . Although some authors have linked increased tinnitus perception to external acoustic meatus occlusion, one study (26) evaluated 50 individuals with bilateral hearing loss and tinnitus, who were fitted with HAs with open cast and cast with relief ventilation (1 mm) and observed that in only 24% of the cases, there was a difference in performance between the two molds, with 12% improved only with the open mold and 12% improved with the mold with relief ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the great majority of cases of tinnitus are of auditory origin, and there are, in these cases, greater difficulties in attendance (4,5) . Intervention for tinnitus has been actively investigated, however, there is still no proven means to guarantee the elimination of this symptom (6) . Its clinical evaluation mainly depends on the self-report of the individual, which may hinder objective interpretations and definition of a better intervention (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Although the cure for tinnitus is being actively investigated, currently, there are no proven ways to eliminate this symptom (28) .…”
Section: Discussionmentioning
confidence: 99%